Variants of LYST and novel STK4 gene mutation in a child with accelerated Chediak Higashi syndrome - Abu Bakar, Asrar; Shunmugarajoo, Haema; Nachiappan, Jeyaseelan P.; Ismail, Intan Hakimah (The Korean Society of Pediatric Infectious Diseases, 2024)
Chediak-Higashi syndrome (CHS) is a rare haematological and immunodeficiency disorder that occurs in childhood leading to recurrent infections, bleeding tendencies and progressive neurological dysfunction. Partial oculocutaneous albinism occurs in almost all cases. The exact prevalence is unknown, and the disease is caused by over 70 identified mutations in the lysosomal trafficking regulator gene. The presence of a bright polychromatic appearance from hair shaft and abnormally large intracytoplasmic granules, especially within neutrophils and platelets in the bone marrow is highly suggestive. Treatment is largely supportive, and the only curative treatment is through an allogeneic hematopoietic stem cell transplant. Without transplant, most patients will enter an accelerated phase of hemophagocytic lymphohistiocytosis (HLH) which carries a high mortality rate. We present a young male with CHS who we had followed through and eventually developed a fulminant accelerated phase. We believe this is only the second reported case of CHS in Malaysia.